2014
DOI: 10.1074/jbc.m113.528257
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Identification and Functional Characterization of the Human Colonic Thiamine Pyrophosphate Transporter

Abstract: Background: Human colonocytes possess a specific, high-affinity, and regulated carrier-mediated system for TPP uptake. Results: Human SLC44A4 protein functions as a TPP transporter. Conclusion: The SLC44A4-mediated TPP uptake system may play a role in the absorption of the microbiota-generated TPP in colon. Significance: Molecular identification of the colon-specific TPP uptake system is important for understanding the mechanisms of overall thiamine nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 33 publications
6
60
0
Order By: Relevance
“…Thiamine (vitamin B1) serves an essential role as a co-factor of enzymes involved in cellular metabolic pathways (13-14); however, it cannot be synthesized de novo in mammalian cells and must be obtained through dietary and microbiota-generated sources. A recently published report demonstrated that SLC44A4 is involved in transport of the phosphorylated form of thiamine (thiamine pyrophosphate) produced by microbiota in the intestine (9). Such a functional role would be consistent with the expression we observed within normal tissues of the gastrointestinal tract, although thiamine pyrophosphate was not one of the substrates we tested for uptake.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Thiamine (vitamin B1) serves an essential role as a co-factor of enzymes involved in cellular metabolic pathways (13-14); however, it cannot be synthesized de novo in mammalian cells and must be obtained through dietary and microbiota-generated sources. A recently published report demonstrated that SLC44A4 is involved in transport of the phosphorylated form of thiamine (thiamine pyrophosphate) produced by microbiota in the intestine (9). Such a functional role would be consistent with the expression we observed within normal tissues of the gastrointestinal tract, although thiamine pyrophosphate was not one of the substrates we tested for uptake.…”
Section: Discussionsupporting
confidence: 70%
“…Although this family of proteins is thought to be involved in choline transport, only SLC44A1 and SLC44A2 have been demonstrated to have choline transport activity (1-7). SLC44A4 has not been shown to be involved in choline transport, but it has been linked with acetylcholine synthesis and transport (8) as well as uptake of thiamine pyrophosphate, the phosphorylated form of vitamin B1 (9).…”
Section: Introductionmentioning
confidence: 99%
“…2e). Low thiamine blood levels have been linked to complications of T1DM 48 and colonic uptake transporters of thiamine have been described 49 . However, the observed patterns in transcript abundances of thiazole synthase and plasma thiamine levels were not correlated in the small subset of individuals who did not take thiamine supplements, precluding any conclusions (Supplementary Section 18 and Supplementary Fig.…”
Section: Human Protein Excretion In T1dm and Microbial Functionsmentioning
confidence: 99%
“…Bacterial sources of thiamine refer to the vitamin that is generated by the colonic microbiota, which exists in the free and the diphosphorylated (TPP) forms (2,7,8,15). Studies from our laboratory have shown that both forms of the vitamin can be captured by colonic epithelial cells (13,14,23). Free thiamine can be taken up by colonocytes via a specific and highly efficient process with characteristics that closely resemble those for the thiamine uptake process occurring in the small intestine (reviewed in Refs.…”
mentioning
confidence: 98%